2021
DOI: 10.3390/w13243618
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Combined Effects of Rising Temperature and Pesticide Contamination on the Swimming Behaviour of Alpine Chironomids

Abstract: Some pollutants can be transported through the atmosphere and travel medium–long distances to be deposited in glaciers at high altitude and latitude. The increase in the rate of glacier melting due to global warming can release these pollutants in alpine streams. This study investigated the combined effects of rising temperatures and chlorpyrifos (CPF) contamination on the swimming behaviour of alpine chironomids collected in a shrinking alpine glacier. We assessed the individual and interaction effects of ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Moreover, organisms in glacial streams are continuously exposed to contaminants released during the melting season. Recent evidence of induced behavioural changes by CPY under different thermal conditions (Lencioni et al, 2021b) have demonstrated the harmful combined effect of chemical and physical stressors.…”
Section: Tablementioning
confidence: 99%
“…Moreover, organisms in glacial streams are continuously exposed to contaminants released during the melting season. Recent evidence of induced behavioural changes by CPY under different thermal conditions (Lencioni et al, 2021b) have demonstrated the harmful combined effect of chemical and physical stressors.…”
Section: Tablementioning
confidence: 99%